Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 910 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Ilex verticillata (L.) A.Gray", "Geometry POLYGON((-156.09 -6.50,-156.09 67.03,-2.37 67.03,-2.37 -6.50,-156.09 -6.50))", "HasGeospatialIssue is false" ] } The dataset includes 910 records from 35 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0016955-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences